APPLICATION OF NEUROFEEDBACK DEVICES IN COGNITIVE PERFORMANCE ENHANCEMENT AND TRACKING LEARNING PATTERNS IN SPORTS - Nagy, Gergely; Csukonyi, Csilla (Stadium - Hungarian Journal of Sport Sciences, 2025)
We examined the current research and studies regarding the neurofeedback trainings, including neurofeedback protocols and available technologies and devices. The results show that neurofeedback training can enhance effectively the cognitive abilities of athletes such as, attention, concentration, reaction time, stress tolerance, and mental toughness. The results may provide helpful information for practitioner specialists and researchers in the applied field.